Morphological tuning via structural modulations in AIE luminogens with the minimum number of possible variables and their use in live cell imaging1. Issue 44 (4th June 2015) - Singh, Roop Shikha; Gupta, Rakesh Kumar; Paitandi, Rajendra Prasad; Dubey, Mrigendra; Sharma, Gunjan; Koch, Biplob; Pandey, Daya Shankar
<x xml:space="preserve">Abstract</x> We present three novel AIE luminogens based on a quinoline–BODIPY platform with strategic tuning of the morphology and optical properties of the nanoaggregates.